Semilinear elliptic equations for the fractional Laplacian with Hardy potential. (April 2020) - Fall, Mouhamed Moustapha
Abstract: In this paper we study existence and nonexistence of nonnegative distributional solutions for a class of semilinear fractional elliptic equations involving the Hardy potential.